Development of a risk prediction model for gastrointestinal adverse events associated with semaglutide administration in patients with type 2 diabetes mellitus - Yue, Deyong; Hua, Xuesheng; Zhu, Ling; Wang, Jun; Gu, Lihua; Yuan, Zhengxia; Jian, Wenle; Chen, Yirong; Meng, Guoliang (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to identify the risk factors associated with gastrointestinal adverse events induced by semaglutide in patients with type 2 diabetes mellitus (T2DM) and to develop a predictive risk model.MethodsA total of 215 patients with T2DM admitted to our hospital between June 2022 and December 2024 were enrolled. Participants were divided into two groups based on the presence (n = 41) or absence (n = 174) of gastrointestinal adverse events associated with semaglutide use. Univariate and multivariate logistic regression analyses were performed to identify significant risk factors for these adverse events. Subsequently, a nomogram was developed using R software to predict the likelihood of gastrointestinal adverse events in this patient population. The predictive performance of the nomogram was assessed using receiver operating characteristic (ROC) curves, calibration plots, and the Hosmer–Lemeshow goodness-of-fit test.ResultsIn a cohort of 215 patients with T2DM, 41 individuals (19.07%) experienced gastrointestinal adverse events attributed to semaglutide administration. Logistic regression analysis identified concomitant gastrointestinal disorders [95% confidence interval (CI): 2.074–9.808, P < 0.001], alcohol consumption (95% CI: 1.304–6.633, P = 0.009), and concurrent use of α-glucosidase inhibitors (95% CI: 1.368–6.460, P = 0.006) as independent risk factors for semaglutide-induced gastrointestinal adverse events in this population. The predictive model demonstrated an area under the ROC curve of 0.763 (95% CI: 0.691–0.836). Calibration assessment revealed a slope approximating unity, and the Hosmer–Lemeshow goodness-of-fit test indicated an adequate model fit (χ² = 5.633, P = 0.228).ConclusionPatients with T2DM exhibit a significant incidence of gastrointestinal adverse events associated with semaglutide use. The presence of gastrointestinal comorbidities, alcohol consumption, and α-glucosidase inhibitor therapy are independent risk factors. The developed nomogram effectively predicts the likelihood of semaglutide-related gastrointestinal adverse events in this patient population.